If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-7x + -7) = -84 Reorder the terms: -2(-7 + -7x) = -84 (-7 * -2 + -7x * -2) = -84 (14 + 14x) = -84 Solving 14 + 14x = -84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 14x = -84 + -14 Combine like terms: 14 + -14 = 0 0 + 14x = -84 + -14 14x = -84 + -14 Combine like terms: -84 + -14 = -98 14x = -98 Divide each side by '14'. x = -7 Simplifying x = -7
| x/8.38=5/100 | | -2(-7-7)=-84 | | 1/2x-3/4=1/3x+7/5 | | 2e^5=9 | | -8+1x= | | 3(8+6x)=240 | | 5/100=x/8.38 | | e(x+7)=26 | | -3+6+2g=45 | | 6ln(6p)=12 | | 5/100=8.38/x | | -4(-4+5x)=36 | | x^2-16=-63 | | (X+4)(x+3)=25 | | 2x-6=-6x+90 | | -27/-3 | | 0,9x-7,4=-0,4x+4,3 | | -3x-6=-6+3x | | 2e^5*x=9 | | 5x+2yi=-15+8i | | 2+86=180 | | 2x-5/-3=11 | | -143=14k | | 2e^5x=9 | | 7x-3=78-2x | | 7-3x/4=34 | | 2x-2=22-4x | | 8x^2-23x-36=0 | | ln(a-10)-1=0 | | 5x+10-x=10 | | 7-3x=6x-56 | | 4(4x+1)=4x-7x |